2021
DOI: 10.1002/cncr.33565
|View full text |Cite
|
Sign up to set email alerts
|

Unhealthy behaviors after breast cancer: Capitalizing on a teachable moment to promote lifestyle improvements

Abstract: Background This study assessed the prevalence and risk factors of unhealthy behaviors among survivors of early‐stage breast cancer. Methods Women (n = 9556) from the CANcer TOxicity cohort (NCT01993498) were included. Physical activity (PA), tobacco and alcohol consumption, and body mass index were assessed at diagnosis and at years 1 and 2 after diagnosis. A behavior was defined as unhealthy if patients failed to meet PA recommendations (≥10 metabolic equivalent task hours per week), reduce/quit tobacco, or d… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
20
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 16 publications
(23 citation statements)
references
References 42 publications
2
20
1
Order By: Relevance
“…Previous studies revealed that health-related behaviors differ according to these stages of survivorship [ 9 ], and inappropriate health-related behaviors increase as the duration of the disease increases [ 10 , 11 ] Health-related behaviors such as smoking, drinking alcohol, and physical activity are defined by the International Agency for Research on Cancer (IARC) as carcinogenic factors for gynecological cancers such as ovarian and uterine cancers, and breast cancers [ 12 ]. Inappropriate health-related behaviors have been reported to affect the occurrence of mental health problems [ 13 , 14 , 15 ].…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…Previous studies revealed that health-related behaviors differ according to these stages of survivorship [ 9 ], and inappropriate health-related behaviors increase as the duration of the disease increases [ 10 , 11 ] Health-related behaviors such as smoking, drinking alcohol, and physical activity are defined by the International Agency for Research on Cancer (IARC) as carcinogenic factors for gynecological cancers such as ovarian and uterine cancers, and breast cancers [ 12 ]. Inappropriate health-related behaviors have been reported to affect the occurrence of mental health problems [ 13 , 14 , 15 ].…”
Section: Introductionmentioning
confidence: 99%
“…A previous study revealed that smokers who experienced cancer reported severe psychological distress more frequently due to depression and anxiety compared to nonsmokers who experienced cancer [ 16 ], and the higher the depression score, the higher the risk of drinking in breast cancer survivors [ 15 ]. In addition, physical activity promotes the release and synthesis of serotonin as well as improvements of physical symptoms such as fatigue and pain, thereby reducing anxiety and depressive symptoms [ 17 ].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Among those that pursued healthy changes, these mostly seemed to happen in the closer aftermath of diagnosis. In contrast, among those with unhealthy lifestyles (41.7% were physically inactive, 18.2% were current smokers, 14.6% consumed alcohol daily, and 48.9% were overweight or obese), these seemed to persist over time, with distinct determinants and risk factors [60 ▪ ]. Bøhn et al evaluated adherence to general lifestyle recommendations, including physical activity, healthy weight management, daily consumption of fruits and vegetables and smoking habit, among young cancer survivors (below 39 years of age).…”
Section: Discussion and Perspectivesmentioning
confidence: 94%
“…Nevertheless, uptake of healthy behaviors is not ubiquitous across survivors 41 . We previously explored this dimension in the CANTO cohort and observed that (1) a nonnegligible proportion of survivors engages or persists in unhealthy behaviors, such as insufficient physical activity, and gain weight, and (2) specific risk factors linked to these unhealthy behaviors can be identified 42 …”
Section: Discussionmentioning
confidence: 99%